2022
DOI: 10.1155/2022/2448010
|View full text |Cite
|
Sign up to set email alerts
|

Intrusion Detection Model for Wireless Sensor Networks Based on MC-GRU

Abstract: A crucial line of defense for the security of wireless sensor network (WSN) is intrusion detection. This research offers a new MC-GRU WSN intrusion detection model based on convolutional neural networks (CNN) and gated recurrent unit (GRU) to solve the issues of low detection accuracy and poor real-time detection in existing WSN intrusion detection algorithms. MC-GRU uses multiple convolutions to extract network data traffic features and uses the high-level features output after convolution operations as input… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The outcomes of a 5-Folds Cross Validation are presented in Table 5. In order to compare the performance of the proposed ML RF approach with DL based approaches, a pervious study proposed by Zhou et al 18 is used. Their study has been selected as it was the only study that we found…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The outcomes of a 5-Folds Cross Validation are presented in Table 5. In order to compare the performance of the proposed ML RF approach with DL based approaches, a pervious study proposed by Zhou et al 18 is used. Their study has been selected as it was the only study that we found…”
Section: Resultsmentioning
confidence: 99%
“…7. Comparing best performance results with a deep learning based intrusion detection approach from the literature 18 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Jingjing et al 27 provided an MCGRU WSN intrusion detection model centered on convolutional neural networks (CNN) along with gated recurrent units (GRU), which resolved the problems of lower detection accuracy as well as deprived real‐time detection. The experiment outcomes centered on the WSN‐DS dataset exhibited that the whole detection accuracy of the different kinds of attack of an black hole, gray hole, flooding, along with scheduling and normal behaviors attained 99.57%.…”
Section: Related Workmentioning
confidence: 99%
“…In WSN, intrusion detection is imperative due to high data transfer. To address low accuracy resulting from attacks in WSN, the Multiple Convolutional and Gated Recurrent Unit (MC-GRU) method is employed ( Jingjing et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%